2017
DOI: 10.1016/s0140-6736(17)30067-3
|View full text |Cite|
|
Sign up to set email alerts
|

Intensive speech and language therapy in patients with chronic aphasia after stroke: a randomised, open-label, blinded-endpoint, controlled trial in a health-care setting

Abstract: German Federal Ministry of Education and Research and the German Society for Aphasia Research and Treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
166
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(210 citation statements)
references
References 27 publications
8
166
0
20
Order By: Relevance
“…As outlined elsewhere, the therapist was blind as to whether individual patients were assigned to the rTMs or to the sham condition. We followed the SLT protocol as proposed and outlined elsewhere [6]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As outlined elsewhere, the therapist was blind as to whether individual patients were assigned to the rTMs or to the sham condition. We followed the SLT protocol as proposed and outlined elsewhere [6]. …”
Section: Methodsmentioning
confidence: 99%
“…The authors also observed that SLT at higher intensity and duration produced greater improvement though in these trials the dropout rate was also higher. Breitenstein et al [6] reported results from a multicenter, blinded-end point and controlled trial. They compared 2 conditions, 3 or more weeks of intensive SLT (10 or more hours per week), compared to a 3-week deferral of intensive SLT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although none of the clinical RCTs conducted in chronic aphasia comprised measurement of brain correlates before and after therapy, a promising heuristic is provided by efficient intensive interventions in chronic PSA patients. In fact, some intensive interventions have proved to lead to significant and consistent improvements of language performance (Brady et al, 2016; Breitenstein et al, 2017) and may therefore be good candidates to study neuroplasticity.…”
Section: Understanding the Neuronal Mechanisms Underlying Language Rementioning
confidence: 99%
“…, Breitenstein et al . ). It is well known that therapy leads to the most favourable outcomes when delivered at high frequency (Bhogal et al .…”
Section: Introductionmentioning
confidence: 97%